Global sourcing and supply management excellence in China : procurement guide for supply experts - Helmold, Marc; Terry, Brian (Management for professionals., 2017)
This book provides readers a holistic and pragmatic approach towards supply management in China. It elaborates on how supply management should integrate the optimum level, and a combination of quality, cost and delivery. In addition to serving as a guide on how to address cultural barriers, apply supply tools and concepts, it also illustrates the best practices in supply management in China. It draws from a large number of best practices of companies from automotive to railway, to convince other functional departments and higher management that supply management plays the most fundamental role in any organization due to the high number of value adding activities which are coming from suppliers. These practices have been derived by a multi-methodical approach including interviews with supply management leaders from industry and experts in academia, making it as unique and a suitable a guide for practitioners and academics.